Dual microcather-dual detachable coil technique in embolization for a congenital intrahepatic portosystemic venous shunt (IPSVS). Issue 5 (September 2013) - Suzuki, Kazushi; Shimohira, Masashi; Hashizume, Takuya; Suzuki, Yosuke; Shibamoto, Yuta
Abstract: We report a 14-year-old boy with a large intrahepatic portosystemic venous shunt. The shunt seemed to be difficult to coil embolize because it was so large and short. However, it was successfully treated by coil embolization with a new dual microcatheter-dual detachable coil technique.